Successful conservative management of ectopic pregnancy in caesarean section scar. (24th December 2012) - Al-Hashimi, Sara; Maiti, Sachchidananda; Macfoy, Donald
Abstract : Caesarean scar pregnancy is a rare type of ectopic pregnancy. The authors present a 24-year-old woman 5 weeks after her last menstrual period. She had a history of a single caesarean section which was followed by a normal vaginal delivery. Ultrasound imaging revealed a pregnancy in her lower segment caesarean section scar. The decision on the choice of treatment was influenced mainly by the β-human chorionic gonadotropin levels in the patient's blood. Although a few reports have been published on similar cases, spontaneous resolution of a caesarean scar ectopic pregnancy of less than 5 weeks gestation is yet to be reported. The patient is now asymptomatic and her urine pregnancy test has been confirmed negative.